Das relações domiciliares ao mercado de trabalho: uma análise da situação das mulheres migrantes no destino - Raquel Aline Schneider (2020)
The economic factor is recognized as the main driver of migration. One of the effects of this finding was to assume migration as a male action, with women doing it, mostly, passively. This assumption limited the understanding of the migration phenomenon and covered up elements related to women's migration. This thesis aimed to contribute to fill these gaps. It started by revisiting the main theoretical approaches to migration with a focus on how female migration was treated, given the lack of a literature that would indicate how women's migration was represented by different approaches. Afterwards, a case study was carried out to verify if there was a feminization of migration from the Northeast-São Paulo and Minas Gerais-São Paulo flows, between the 1980s and 2000s. The analyzes were made through the 1991, 2000 and 2010 Demographic Censuses. In order to verify whether there was feminization over the period, the participation of women in the flows was considered. In sequence, an algorithm was elaborated, which uses the household strucuture of recent in-migrants (with less than two years of residence in São Paulo), as a proxy for the type of migration made, whether individual or joint, indicating the degree of independence of the displacement. It ended with the analysis of the situation of migrants in the labor market in the destination, through a descriptive analysis of their characteristics and the estimation of income by linear and quantile regressions. The results showed that the distribution of immigrants was balanced between the sexes, with women originating in Minas Gerais being just over half and increasing their participation over the period, while in the flow originated in the Nordeste there was no tendency to increase the participation of women. Regarding the type of migration made, it was found that the majority of recent immigrants made a joint move. There was a drop in the participation of those who made individual migration among those originating in the Nordeste and, among those originating in Minas Gerais, a small increase. Although there were no major changes in the period, it was found that the way migrant women moved is very similar to that of men, a result that was not in line with the literature, which indicated that women carried out a more joint migration, associated with family. The results of the characteristics of immigrant women in São Paulo, who participated in the labor market, showed improvements such as a higher level of education, an increase in the activity rate, formality and income in the period, with the origin of immigrants being, once more, a differentiation factor. With regard to women originating in Minas Gerais, the increased participation of women in the flow, the greater participation of those who moved individually and the relative improvement in the labor market, which brought their condition closer to those born in São Paulo (the best positioned group) indicated a feminization of the flow. What was not verified in the Nordeste-São Paulo flow, there was no increase in female participation, there was a reduction in individual migration and the gap in the labor market, in relation to immigrants of Minas Gerais origin and the natural ones, it remained almost intact.